Changes of mitochondria in the contractile cardiomyocytes during postnatal rat ontogenesis. - Kozlov, S. V.; Mayevsky, A. E.; Mіshalov, V. D.; Sulayeva, O. N. (Морфологія / Morphologia / Morfologìâ, 2014)
Background. CVDs are the number 1 cause of death globally: more people die annually from CVDs than from any other cause. An estimated 17.5 million people died from CVDs in 2012, representing 31% of all global deaths. Of these deaths, an estimated 7.4 million were due to coronary heart disease and 6.7 million were due to stroke. Over three quarters of CVD deaths take place in low- and middle-income countries. Objective. Ultrastructural analysis of mitochondria in the rat contractile cardiomyocytes during postnatal ontogenesis. Methods. As the object of the study were used neonatal rat hearts, on the 5th, 10th, 15th, 30th days of life and mature animals. Hearts were investigated by the transmission electron microscopy. Volume density and numerical density of mitochondria were estimated. The Paired Student’s t-test was applied. Results. Was conducted a comprehensive ultrastructural analysis of mitochondria contractile cardiomyocytes, which allowed us to determine changes in the qualitative and quantitative parameters of mitochondria during postnatal ontogenesis, and helps to explain the dynamics and the development of mitochondria heart muscles cells after birth. Conclusion. It was shown that from the 1st to the 5th day there was a significant increase in volume density of mitochondria, which was accompanied by the increasing complexity of the ultrastructural organization of organelles. Following 20th day of postnatal ontogenesis mitochondrial structure was approaching the definitive condition and on the 30th day was the same as the mature myocardium.